2019
DOI: 10.1177/0013164419871659
|View full text |Cite
|
Sign up to set email alerts
|

A Bayesian Random Block Item Response Theory Model for Forced-Choice Formats

Abstract: Based on the framework of testlet models, the current study suggests the Bayesian random block item response theory (BRB IRT) model to fit forced-choice formats where an item block is composed of three or more items. To account for local dependence among items within a block, the BRB IRT model incorporated a random block effect into the response function and used a Markov Chain Monte Carlo procedure for simultaneous estimation of item and trait parameters. The simulation results demonstrated that the BRB IRT m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…Since the intercept parameter of the TIRT model has a different meaning from the parameter of the 2PL-RANK model, in the next analysis, we compare only the estimation results of the discrimination  parameters, 24 trait correlations, and thetas. The correlation coefficient between the two models was 0.934 for the discrimination parameter, this value slightly higher than the results reported by Lee and Smith (2020) The scale reliabilities (Table 5) were calculated using the marginal reliability equation (Brown & Croudace 2015), and CORR and ABS were calculated for each dimension. The mean of reliabilities of 2PL-RANK is slightly higher than TIRT.…”
Section: Real Data Analysismentioning
confidence: 59%
See 2 more Smart Citations
“…Since the intercept parameter of the TIRT model has a different meaning from the parameter of the 2PL-RANK model, in the next analysis, we compare only the estimation results of the discrimination  parameters, 24 trait correlations, and thetas. The correlation coefficient between the two models was 0.934 for the discrimination parameter, this value slightly higher than the results reported by Lee and Smith (2020) The scale reliabilities (Table 5) were calculated using the marginal reliability equation (Brown & Croudace 2015), and CORR and ABS were calculated for each dimension. The mean of reliabilities of 2PL-RANK is slightly higher than TIRT.…”
Section: Real Data Analysismentioning
confidence: 59%
“…This research had some limitations. Foremost, since to verify the advantages of the stEM method in high-dimensional contexts, we only simulated 12-and 24-dimensional test scenarios, while previous simulation studies (Lee & Smith, 2020;Lee et al, 2019;Morillo et al, 2016) were limited by the time-consuming nature of traditional parameter estimation method, and most of their simulation conditions were in 10 dimensions and below. Although most of the established personality tests are high-dimensional (SHL 2018;Aon Hewitt, 2015), the performance of this model and algorithm in low-dimensional contexts needs to be further investigated if the 2PL-RANK model is to be used in lower dimensional assessment contexts(like Big Five personality scale tests).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various simulation studies have demonstrated that normative scores can indeed be obtained by means of TIRT (or comparable) modeling approaches (Brown & Maydeu-Olivares, 2011;Bürkner, Schulte, & Holling, 2019;H. Lee & Smith, 2020;Schulte, Holling, & Bürkner, 2020), although satisfactory estimation accuracy cannot easily be achieved under all practically relevant conditions (see Section 1.2 for details).…”
Section: Obtaining Normative Traits Scores From Comparative Judgmentsmentioning
confidence: 99%
“…On the other hand, existing research suggests that, with few exception discussed below, including unequally keyed item pairs is required to obtain normative trait scores from FC questionnaires (Brown & Maydeu-Olivares, 2011;Bürkner, Schulte, & Holling, 2019;H. Lee & Smith, 2020;Schulte, Holling, & Bürkner, 2020).…”
Section: The Paradox Of Comparative Judgements In High-stakes Situationsmentioning
confidence: 99%